A method for preparing active light nano calcium carbonate

By using aromatic polyester polyols and aluminates as surface treatment agents in the carbonation process for preparing light calcium carbonate, the problems of high energy consumption and agglomeration in existing technologies have been solved, achieving efficient preparation of active light calcium carbonate and improving its compatibility and dispersibility in organic polymers.

CN115974125BActive Publication Date: 2025-01-10XUANCHENG XIN WEIHUA CHEM SCI & TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211669506.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-24
Publication Date
2025-01-10
Estimated Expiration
2042-12-24

AI Technical Summary

Technical Problem

Existing methods for preparing light calcium carbonate by carbonation have drawbacks such as high energy consumption, high equipment costs, and the prepared light calcium carbonate is prone to agglomeration in organic polymer systems, leading to a decline in performance.

Method used

Aromatic polyester polyols and aluminates are used as surface treatment agents. After being mixed and stirred evenly by ultrasonication, they are mixed with calcium carbonate slurry, and then carbonized with a mixture of CO2 and nitrogen gas through a two-fluid atomizing nozzle. The mixture is then dried rapidly to form active lightweight calcium carbonate powder.

Benefits of technology

It improves the compatibility and dispersibility of calcium carbonate in organic polymers, enhances its activity, reduces aggregation and deposition, and improves performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of active light nano calcium carbonate. The method comprises the following steps: 1. crushing calcium oxide powder to 10-50 micrometers, adding the powder into hot water for digestion, and then diluting the powder with water. The method comprises the following steps: the aromatic polyester polyol can synergize with aluminate, so that the aluminate is convenient to be grafted on the surface of calcium carbonate molecules. On the other hand, since the aromatic polyester polyol contains a large number of aromatic rings and various polar groups, the aromatic polyester polyol can interact with calcium carbonate slurry and adhere to the molecules of the calcium carbonate slurry, thereby destroying the hydrogen bonding and intermolecular forces between the molecules of the calcium carbonate slurry, so that the calcium carbonate molecules are not easy to aggregate and deposit. Meanwhile, one end of the aluminate is easy to undergo substitution reaction with the active hydroxyl group on the surface of the calcium carbonate to form a stable chemical bond, and the organic group at the other end can be entangled or chemically combined with the polymer to play the role of an "intermediate bridge", thereby improving the activity of the calcium carbonate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of calcium carbonate preparation, and in particular to a method for preparing active light nano calcium carbonate. Background Art

[0002] As an important inorganic powder material, light calcium carbonate is widely used in plastics, rubber, adhesives, coatings, cosmetics, textiles and sewage purification. The industrial demand is increasing day by day. The preparation methods of light calcium carbonate are mainly carbonization and double decomposition. In addition, there are microemulsion method, emulsion liquid film method and sol-gel method. Carbonization is the core process of nano calcium carbonate production. It is prepared by gas-liquid reaction between CO2 and Ca(OH)2 slurry. In industrial production, the selected limestone is usually calcined to obtain quicklime and kiln gas. The quicklime is digested to obtain Ca(OH)2 suspension; the kiln gas is purified and used as a CO2 source to react with the Ca(OH)2 suspension. After reaching the carbonization end point, the obtained calcium carbonate slurry is dehydrated and dried to obtain the nano calcium carbonate product. Carbonization can effectively utilize mineral resources, is low-cost and environmentally friendly, and is currently the most widely used method in industry.

[0003] At present, the relatively mature carbonization methods for preparing light calcium carbonate include intermittent bubbling carbonization, multi-stage spray carbonization and supergravity carbonization. These methods all have the disadvantages of high energy consumption and high equipment cost. Chinese invention patent CN106587125A also discloses a method for preparing light calcium carbonate, which directly carbonizes a calcium hydroxide suspension and carbon dioxide compressed gas through a two-fluid atomizing nozzle to generate light calcium carbonate and quickly dries to directly obtain powder. However, the light calcium carbonate obtained by this method has poor affinity with organic polymers during use, and agglomerates to form aggregates inside the organic polymer system, resulting in reduced product performance. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a method for preparing active lightweight nano calcium carbonate. The specific technical scheme is as follows:

[0005] A method for preparing active light nano calcium carbonate comprises the following steps: Step 1: crushing calcium oxide powder to 10-50 μm, adding it into hot water for digestion, then diluting it with water, and stirring it at high speed to prepare a calcium hydroxide suspension with a mass percentage concentration of 1-5%;

[0006] Step 2: introducing a gas containing CO2 at 15-25°C for carbonization, wherein the content of CO2 in the gas is maintained between 20% and 35%, and carbonization is performed until the pH value is 6-7 to obtain a calcium carbonate slurry;

[0007] Step 3: After the aromatic polyester polyol is heated and dissolved, it is mixed and stirred evenly with the aluminate by ultrasonication to prepare a surface treatment agent solution;

[0008] Step 4: adding a surface treatment agent solution of 0.7 to 2.0% by weight of the calcium carbonate slurry to the calcium carbonate slurry, stirring evenly, and performing coating treatment for 0.5 to 2 hours to obtain a surface-modified calcium carbonate slurry;

[0009] Step 5: The surface-modified calcium carbonate slurry and the compressed gas mixed with CO2 and nitrogen are respectively passed through a two-fluid atomizing nozzle. While the surface-modified calcium carbonate slurry is dispersed into micron-sized droplets by the high-pressure CO2 and nitrogen mixed gas, a carbonization reaction occurs and the slurry is quickly dried by the hot air flow to directly obtain the active light calcium carbonate powder of the present invention.

[0010] As an improvement of the above technical solution, the aromatic polyester polyol is selected from one or more of phthalic anhydride polyester polyol PS-450, phthalic anhydride polyester polyol PS-550, phthalic anhydride polyester polyol PS-1000 and phthalic anhydride polyester polyol PS-2000.

[0011] As an improvement of the above technical solution, the stirring speed in step 4 is 500-600 r / min.

[0012] As an improvement of the above technical solution, the temperature of the hot air flow used to dry the spray droplets in step 5 is 165-190°C.

[0013] As an improvement of the above technical solution, the volume ratio of the mixed gas of CO2 and nitrogen in step 5 is 2:1.

[0014] As an improvement of the above technical solution, in step 3, the mass ratio of the aromatic polyester polyol to the aluminate is 8:1.

[0015] Beneficial effects of the present invention:

[0016] Aromatic polyester polyols can play a synergistic role with aluminate. On the one hand, it is convenient for aluminate to be grafted on the surface of calcium carbonate molecules. On the other hand, since aromatic polyester polyols contain a large number of aromatic rings and various polar groups, they can interact with calcium carbonate slurry and adhere to the molecules of calcium carbonate slurry, destroying the hydrogen bonds and intermolecular forces between calcium carbonate slurry molecules, making it difficult for calcium carbonate molecules to aggregate and deposit. At the same time, one end of the aluminate is easy to undergo substitution reaction with the active hydroxyl group on the surface of calcium carbonate to form a stable chemical bond, and the organic group at the other end can be entangled or chemically combined with the polymer, playing the role of "intermediate bridge", improving the compatibility and dispersibility of calcium carbonate in organic polymers, thereby improving the activity of calcium carbonate. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0018] Embodiment 1:

[0019] A method for preparing active light nano calcium carbonate comprises the following steps: Step 1: crushing calcium oxide powder to 10 μm, adding it into hot water for digestion, then diluting it with water, and stirring it at high speed to prepare a calcium hydroxide suspension with a mass percentage concentration of 1%;

[0020] Step 2: introducing a gas containing CO2 at 15°C for carbonization, wherein the content of CO2 in the gas is maintained between 20%, and carbonization is performed until the pH value is 6 to obtain a calcium carbonate slurry;

[0021] Step 3: After the aromatic polyester polyol is heated and dissolved, it is evenly mixed and stirred with aluminate by ultrasonication to prepare a surface treatment agent solution, wherein the mass ratio of the aromatic polyester polyol to the aluminate is 8:1, and the aromatic polyester polyol is selected from one or more of phthalic anhydride polyester polyol PS-450, phthalic anhydride polyester polyol PS-550, phthalic anhydride polyester polyol PS-1000 and phthalic anhydride polyester polyol PS-2000. This application uses phthalic anhydride polyester polyol PS-450 as an example.

[0022] Step 4: Add 0.7% of the surface treatment agent solution by weight of the calcium carbonate slurry to the calcium carbonate slurry, stir evenly, and perform coating treatment for 0.5h to obtain a surface modified calcium carbonate slurry, wherein the stirring speed is 500r / min

[0023] Step 5: The surface-modified calcium carbonate slurry and the compressed gas mixed with CO2 and nitrogen are respectively passed through a two-fluid atomizing nozzle. The surface-modified calcium carbonate slurry is dispersed into micron-sized droplets by the high-pressure CO2 and nitrogen mixed gas, and a carbonization reaction occurs at the same time. The slurry is quickly dried by a hot air flow at a temperature of 165° C. to directly obtain the active light calcium carbonate powder of the present invention. The volume ratio of the CO2 and nitrogen mixed gas is 2:1. The two carbonization reactions can fully ensure that the calcium hydroxide suspension is completely converted into a calcium carbonate solution.

[0024] Aromatic polyester polyols can play a synergistic role with aluminate. On the one hand, it is convenient for aluminate to be grafted on the surface of calcium carbonate molecules. On the other hand, since aromatic polyester polyols contain a large number of aromatic rings and various polar groups, they can interact with calcium carbonate slurry and adhere to the molecules of calcium carbonate slurry, destroying the hydrogen bonds and intermolecular forces between calcium carbonate slurry molecules, making it difficult for calcium carbonate molecules to aggregate and deposit. At the same time, one end of the aluminate is easy to undergo substitution reaction with the active hydroxyl group on the surface of calcium carbonate to form a stable chemical bond, and the organic group at the other end can be entangled or chemically combined with the polymer, playing the role of "intermediate bridge", improving the compatibility and dispersibility of calcium carbonate in organic polymers, thereby improving the activity of calcium carbonate.

[0025] Embodiment 2:

[0026] A method for preparing active light nano calcium carbonate comprises the following steps: Step 1: crushing calcium oxide powder to 30 μm, adding it into hot water for digestion, then diluting it with water, and stirring it at high speed to prepare a calcium hydroxide suspension with a mass percentage concentration of 3%;

[0027] Step 2: introducing a gas containing CO2 at 20°C for carbonization, wherein the content of CO2 in the gas is maintained between 40% and the carbonization is performed until the pH value is 6.5 to obtain a calcium carbonate slurry;

[0028] Step 3: After the aromatic polyester polyol is heated and dissolved, it is evenly mixed and stirred with aluminate by ultrasonication to prepare a surface treatment agent solution, wherein the mass ratio of the aromatic polyester polyol to the aluminate is 8:1, and the aromatic polyester polyol is selected from one or more of phthalic anhydride polyester polyol PS-450, phthalic anhydride polyester polyol PS-550, phthalic anhydride polyester polyol PS-1000 and phthalic anhydride polyester polyol PS-2000. This application uses phthalic anhydride polyester polyol PS-450 as an example.

[0029] Step 4: Add 1.6% of the surface treatment agent solution by weight of the calcium carbonate slurry to the calcium carbonate slurry, stir evenly, and perform coating treatment for 1.5 hours to obtain a surface-modified calcium carbonate slurry, wherein the stirring speed is 550 r / min.

[0030] Step 5: The surface-modified calcium carbonate slurry and the compressed gas mixed with CO2 and nitrogen are respectively passed through a two-fluid atomizing nozzle. The surface-modified calcium carbonate slurry is dispersed into micron-sized droplets by the high-pressure CO2 and nitrogen mixed gas, and a carbonization reaction occurs at the same time. The slurry is quickly dried by a hot air flow at a temperature of 177° C., and the active light calcium carbonate powder of the present invention is directly obtained, wherein the volume ratio of the CO2 and nitrogen mixed gas is 2:1.

[0031] Embodiment three:

[0032] A method for preparing active light nano calcium carbonate comprises the following steps: Step 1: crushing calcium oxide powder to 50 μm, adding it into hot water for digestion, then diluting it with water, and stirring it at high speed to prepare a calcium hydroxide suspension with a mass percentage concentration of 5%.

[0033] Step 2: A gas containing CO2 is introduced at 25°C for carbonization, wherein the content of CO2 in the gas is maintained between 35% and the pH value is carbonized to 7 to obtain a calcium carbonate slurry.

[0034] Step 3: After the aromatic polyester polyol is heated and dissolved, it is evenly mixed and stirred with aluminate by ultrasonication to prepare a surface treatment agent solution, wherein the mass ratio of the aromatic polyester polyol to the aluminate is 8:1, and the aromatic polyester polyol is selected from one or more of phthalic anhydride polyester polyol PS-450, phthalic anhydride polyester polyol PS-550, phthalic anhydride polyester polyol PS-1000 and phthalic anhydride polyester polyol PS-2000. This application uses phthalic anhydride polyester polyol PS-450 as an example.

[0035] Step 4: Add 2.0% of the surface treatment agent solution by weight of the calcium carbonate slurry to the calcium carbonate slurry, stir evenly, and perform coating treatment for 2 hours to obtain a surface-modified calcium carbonate slurry at a stirring speed of 600 r / min.

[0036] Step 5: The surface-modified calcium carbonate slurry and the compressed gas mixed with CO2 and nitrogen are respectively passed through a two-fluid atomizing nozzle. The surface-modified calcium carbonate slurry is dispersed into micron-sized droplets by the high-pressure CO2 and nitrogen mixed gas, and a carbonization reaction occurs at the same time. The slurry is quickly dried by a hot air flow at a temperature of 190° C. to directly obtain the active light calcium carbonate powder of the present invention, wherein the volume ratio of the CO2 and nitrogen mixed gas is 2:1.

[0037] Comparative Example 1

[0038] A method for preparing active light nano calcium carbonate comprises the following steps: Step 1: crushing calcium oxide powder to 50 μm, adding it into hot water for digestion, then diluting it with water, and stirring it at high speed to prepare a calcium hydroxide suspension with a mass percentage concentration of 5%.

[0039] Step 2: A gas containing CO2 is introduced at 25°C for carbonization, wherein the content of CO2 in the gas is maintained between 35% and the pH value is carbonized to 7 to obtain a calcium carbonate slurry.

[0040] Step 3: The calcium carbonate slurry and the compressed gas mixed with CO2 and nitrogen are respectively passed through a two-fluid atomizing nozzle, and the calcium carbonate slurry is dispersed into micron-sized droplets by the high-pressure CO2 and nitrogen mixed gas, and a carbonization reaction occurs at the same time, and is quickly dried by a hot air flow at a temperature of 190° C. to directly obtain light calcium carbonate powder, wherein the volume ratio of the CO2 and nitrogen mixed gas is 2:1.

[0041] Comparative Example 2

[0042] A method for preparing active light nano calcium carbonate comprises the following steps: Step 1: crushing calcium oxide powder to 50 μm, adding it into hot water for digestion, then diluting it with water, and stirring it at high speed to prepare a calcium hydroxide suspension with a mass percentage concentration of 5%.

[0043] Step 2: A gas containing CO2 is introduced at 25°C for carbonization, wherein the content of CO2 in the gas is maintained between 35% and the pH value is carbonized to 7 to obtain a calcium carbonate slurry.

[0044] Step 3: Heat and dissolve the aromatic polyester polyol, wherein the aromatic polyester polyol is selected from one or more of phthalic anhydride polyester polyol PS-450, phthalic anhydride polyester polyol PS-550, phthalic anhydride polyester polyol PS-1000 and phthalic anhydride polyester polyol PS-2000. This application uses phthalic anhydride polyester polyol PS-450 as an example.

[0045] Step 4: Add 2.0% of the weight of the calcium carbonate slurry of aromatic polyester polyol to the calcium carbonate slurry, stir evenly, and perform coating treatment for 2 hours to obtain modified calcium carbonate slurry at a stirring speed of 600 r / min.

[0046] Step 5: The modified calcium carbonate slurry and the compressed gas mixed with CO2 and nitrogen are respectively passed through a two-fluid atomizing nozzle. The modified calcium carbonate slurry is dispersed into micron-sized droplets by the high-pressure CO2 and nitrogen mixed gas, and a carbonization reaction occurs. The slurry is quickly dried by a hot air flow at a temperature of 190° C. to directly obtain the active light calcium carbonate powder of the present invention, wherein the volume ratio of the CO2 and nitrogen mixed gas is 2:1.

[0047] Comparative Example 3

[0048] A method for preparing active light nano calcium carbonate comprises the following steps: Step 1: crushing calcium oxide powder to 50 μm, adding it into hot water for digestion, then diluting it with water, and stirring it at high speed to prepare a calcium hydroxide suspension with a mass percentage concentration of 5%.

[0049] Step 2: A gas containing CO2 is introduced at 25°C for carbonization, wherein the content of CO2 in the gas is maintained between 35% and the pH value is carbonized to 7 to obtain a calcium carbonate slurry.

[0050] Step 3: Add 2.0% titanate based on the weight of the calcium carbonate slurry to the calcium carbonate slurry, stir evenly, and perform coating treatment for 2 hours to obtain a surface-modified calcium carbonate slurry at a stirring speed of 600 r / min.

[0051] Step 4: The surface-modified calcium carbonate slurry and the compressed gas mixed with CO2 and nitrogen are respectively passed through a two-fluid atomizing nozzle. The surface-modified calcium carbonate slurry is dispersed into micron-sized droplets by the high-pressure CO2 and nitrogen mixed gas, and a carbonization reaction occurs at the same time. The slurry is quickly dried by a hot air flow at a temperature of 190° C. to directly obtain the active light calcium carbonate powder of the present invention, wherein the volume ratio of the CO2 and nitrogen mixed gas is 2:1.

[0052] Oil absorption detection method:

[0053] The light calcium carbonate samples obtained in Examples 1-3 and the comparative example are placed on a glass plate or a glazed porcelain plate, and dioctyl phthalate (DOP) of known mass is added dropwise using a dropper bottle. During the addition, the sample is continuously turned and ground with a spatula. At first, the sample is dispersed, and then gradually forms a mass until it is completely wetted by DOP. The end point is when a whole mass is formed. The mass of the dropper bottle is weighed to an accuracy of 0.01 g. The entire measurement is required to be completed within 90 minutes. The oil absorption is calculated. The results are shown in the table below.

[0054] Oil absorption ml / 100g Example 1 166 Example 2 177 Example 3 174 Comparative Example 1 60 Comparative Example 2 101 Comparative Example 3 143

[0055] From the above test data, it can be seen that in the present invention, the addition of aromatic polyester polyols and aluminates during the preparation process can significantly increase the oil absorption of light calcium carbonate, and the removal of either aromatic polyester polyols or aluminates will have a significant impact on the oil absorption of light calcium carbonate.

[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing active light nano calcium carbonate, characterized in that: It includes the following steps: Step 1: crush the calcium oxide powder into 10-50 μm, add it into hot water for digestion, then dilute it with water, stir it at high speed to prepare a calcium hydroxide suspension with a mass percentage concentration of 1-5%; Step 2: introducing a gas containing CO2 at 15-25°C for carbonization, wherein the content of CO2 in the gas is maintained between 20% and 35%, and carbonization is performed until the pH value is 6-7 to obtain a calcium carbonate slurry; Step 3: After the aromatic polyester polyol is heated and dissolved, it is mixed and stirred evenly with the aluminate by ultrasonication to prepare a surface treatment agent solution; Step 4: adding a surface treatment agent solution of 0.7 to 2.0% by weight of the calcium carbonate slurry to the calcium carbonate slurry, stirring evenly, and performing coating treatment for 0.5 to 2 hours to obtain a surface-modified calcium carbonate slurry; Step 5: The surface-modified calcium carbonate slurry and the compressed gas mixed with CO2 and nitrogen are respectively passed through a two-fluid atomizing nozzle. The surface-modified calcium carbonate slurry is dispersed into micron-sized droplets by the high-pressure CO2 and nitrogen mixed gas, and a carbonization reaction occurs at the same time. The slurry is quickly dried by the hot air flow to obtain active light nano-calcium carbonate. The aromatic polyester polyol is selected from one or more of phthalic anhydride polyester polyol PS-450, phthalic anhydride polyester polyol PS-550, phthalic anhydride polyester polyol PS-1000 and phthalic anhydride polyester polyol PS-2000; The stirring speed in step 4 is 500-600 r / min; The temperature of the hot air flow used to dry the spray droplets in step 5 is 165-190° C.; In step 5, the volume ratio of the mixed gas of CO2 and nitrogen is 2:1; In the step 3, the mass ratio of the aromatic polyester polyol to the aluminate is 8:1.

Citation Information

Patent Citations

  • Preparation method for light calcium carbonate

    CN106587125A

  • Preparation method of nanoscale activated calcium carbonate for plastic film

    CN112079374A

  • Preparation method of active light calcium carbonate

    CN112875739A